2020
DOI: 10.1016/j.ecoenv.2020.110656
|View full text |Cite
|
Sign up to set email alerts
|

Comparing microplastics contaminants in (dry and raining) seasons for Ox- Bow Lake in Yenagoa, Nigeria

Abstract: The occurrence and distribution of microplastics (MPs) for two seasons (dry and raining) were investigated based on 10 sections of OX-Bow Lake Yenagoa, Nigeria for surface water and sediments. MPs were abundant in colour and dominated by fibrous items. For dry season, Polyethylene terephthalate (PET) and Plasticised polyvinyl chloride (Plasticised PVC) were the predominant MPs; they both account for 72.63% and 10.9% of surface water and sediment samples. The raining season accounted for Plasticised (PVC) 81.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…The small-sized ranged from 0.011 to 0.5315 mm MP abundance was found in the river water bodies; Obiaraedu, Nwangele, Okumpi, Ogbajarajara, and Onuezuze Rivers (Ebere et al 2019 ), Bloukrans River in the eastern periphery of the Mediterranean Sea (Nel et al 2018 ), Bloukrans River (Nel et al 2019 ). The size of MP abundance from the three studied lakes, Oxbow Lake (Biginagwa et al 2016 ), Eleyele Lake (Adeogun et al 2020 ), and Victoria Lake (Oni et al 2020 ) have been recorded as 2.41, 0.827, and < 0.5 mm, respectively. More or less, the estuaries, coastlines, bays, and gulfs of the Mediterranean Sea and the Atlantic Ocean have been observed that a similar length of MP abundance ranged from 0.63 to 2.6 mm.…”
Section: Physical and Structural Characteristics Of Microplastics In The African Water Systemmentioning
confidence: 95%
See 3 more Smart Citations
“…The small-sized ranged from 0.011 to 0.5315 mm MP abundance was found in the river water bodies; Obiaraedu, Nwangele, Okumpi, Ogbajarajara, and Onuezuze Rivers (Ebere et al 2019 ), Bloukrans River in the eastern periphery of the Mediterranean Sea (Nel et al 2018 ), Bloukrans River (Nel et al 2019 ). The size of MP abundance from the three studied lakes, Oxbow Lake (Biginagwa et al 2016 ), Eleyele Lake (Adeogun et al 2020 ), and Victoria Lake (Oni et al 2020 ) have been recorded as 2.41, 0.827, and < 0.5 mm, respectively. More or less, the estuaries, coastlines, bays, and gulfs of the Mediterranean Sea and the Atlantic Ocean have been observed that a similar length of MP abundance ranged from 0.63 to 2.6 mm.…”
Section: Physical and Structural Characteristics Of Microplastics In The African Water Systemmentioning
confidence: 95%
“…These processes have been used to remove interfering organic tissues and inorganic dust also. In this review, the degradation of impurities in the samples was found oxidation with potassium hydroxide (KOH) (Sparks 2020 ; Adika et al 2020 ; Shabaka et al 2020 ; Dahms et al 2020 ), hydrogen peroxide (H 2 O 2 ) (Adeogun et al 2020 ; Oni et al 2020 ; Vilakati et al 2020 ), and sodium hydroxide (NaOH) (Biginagwa et al 2016 ). KOH and H 2 O 2 are most popular and reportedly found in the retrieved literature as well as worldwide used for effective treatment processes as an oxidizing agent.…”
Section: Sampling Techniques Mps Preparations and Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nigeria reportedly generated 42 million tons of solid waste of the total 62 million tons generated by Sub-Saharan Africa [106,107]. About 20% of the landfills in Nigeria is waste from polythene materials, plastic water bottles, water sachets, and plastic bags [108][109][110]. Lagos alone contributes 450,000 tons of plastic waste that enter into the ocean environment annually [111].…”
Section: Microplastics In Fishmentioning
confidence: 99%